2009
DOI: 10.1177/0272989x09342747
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Population Preferences for Mass Colorectal Cancer Screening Organization

Abstract: The results demonstrate that the discrete choice experiment provides information on patient preferences for CRC screening: improving screening program effectiveness, for instance, by improving test sensitivity (the most valued attribute) would increase satisfaction among the general population with regard to CRC screening programs. Additional studies are required to study how patient preferences actually affect adherence to regular screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 28 publications
5
49
1
1
Order By: Relevance
“…Patients undergoing colonoscopy were less satisfied than those undergoing CT colonography (median score of 61 and interquartile range [IQR] of 55-67 vs median score of 64 and IQR of 58-70, respectively; P = .008) and significantly more worried (median score of 16 [IQR,[12][13][14][15][16][17][18][19][20][21] vs 15 [IQR, [9][10][11][12][13][14][15][16][17][18][19], P = .007); they also experienced more physical discomfort (median score of 39 [IQR, 29-51] vs 35 [IQR,) and more adverse events (82 of 246 vs 28 of 122 reported feeling faint or dizzy, P = .039). However, at 3 months, they were more satisfied with how results were received (median score of 4 [IQR, [3][4] vs 3 [IQR, , P , .0005) and less likely to require follow-up colonic investigations (17 of 230 vs 37 of 107, P , .0005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing colonoscopy were less satisfied than those undergoing CT colonography (median score of 61 and interquartile range [IQR] of 55-67 vs median score of 64 and IQR of 58-70, respectively; P = .008) and significantly more worried (median score of 16 [IQR,[12][13][14][15][16][17][18][19][20][21] vs 15 [IQR, [9][10][11][12][13][14][15][16][17][18][19], P = .007); they also experienced more physical discomfort (median score of 39 [IQR, 29-51] vs 35 [IQR,) and more adverse events (82 of 246 vs 28 of 122 reported feeling faint or dizzy, P = .039). However, at 3 months, they were more satisfied with how results were received (median score of 4 [IQR, [3][4] vs 3 [IQR, , P , .0005) and less likely to require follow-up colonic investigations (17 of 230 vs 37 of 107, P , .0005).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown sensitivity to be important when patients form preferences for colorectal investigations, both in diagnostic (19) and screening (20)(21)(22) contexts. It is possible that participants would rate CT colonography less positively if aware that it may be less sensitive than colonoscopy (23).…”
Section: Gastrointestinal Imaging: Patient Experience With Colonic Exmentioning
confidence: 99%
“…Previous research has found sensitivity to be important when patients form preferences for colorectal investigations, both in symptomatic 78 and screening contexts. [101][102][103] It is possible that participants would rate CTC less positively if aware that it may be less sensitive than colonoscopy. 15 Observations may also have been influenced by centre-to-centre variation in bowel preparation, sedation/analgesia and gas insufflation.…”
Section: Health Psychology Assessmentmentioning
confidence: 99%
“…the period between screening invitations), CRC mortality risk reduction, test specificity (the proportion of people without abnormalities who are correctly categorised as such) and financial costs [24]. Other perspectives included improving service users' satisfaction [19] or fulfilling an ethical duty to involve service users in healthcare decisions [23].…”
Section: Study Aims and Perspectivesmentioning
confidence: 99%
“…sensitivity, "unnecessary colonoscopies" or "accuracy" [21][22][23]) or CRCmortality risk reduction [18,20]). Two studies provided information on both accuracy and CRC-mortality risk reduction [19,23].…”
Section: Attributes and Levelsmentioning
confidence: 99%